The APC/C Ubiquitin Ligase: From Cell Biology to Tumorigenesis - Penas, Clara; Ramachandran, Vimal; Ayad, Nagi G. (Frontiers in Oncology, 2012)
The ubiquitin proteasome system (UPS) is required for normal cell proliferation, vertebrate development, and cancer cell transformation. The UPS consists of multiple proteins that work in concert to target a protein for degradation via the 26S proteasome. Chains of an 8.5 kDa protein called ubiquitin are attached to substrates, thus allowing recognition by the 26S proteasome. Enzymes called ubiquitin ligases or E3s mediate specific attachment to substrates. Although there are over 600 different ubiquitin ligases, the Skp1-Cullin-F-box proteins (SCF) ubiquitin ligases and the Anaphase Promoting Complex/cyclosome (APC/C) are the most studied. SCF involvement in cancer has been known for some time while APC/C’s cancer role has recently emerged. In this review we will discuss the importance of APC/C to normal cell proliferation and development, thus underscoring its possible contribution to transformation. We will also put forth the hypothesis that modulating a specific interaction of the APC/C may be therapeutically attractive in specific cancer subtypes. Finally, given that the APC/C pathway is relatively new as a cancer target, therapeutic interventions affecting APC/C activity may be beneficial in cancers that are resistant to classical chemotherapy.